Analisis Kritis Terhadap Konsep Kesetaraan Gender dalam Himpunan Putusan Tarjih Muhammadiyah - Fahreza Nur Salsabila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to critically analyze the concept of keluarga sakinah in the Himpunan Putusan Tarjih Muhammadiyah (HPT) by examining the representation of gender relations and its alignment with the principle of gender equality in Islam. This research employs a qualitative library-based approach using an analytical-critical method. The primary data consist of the HPT document, which is analyzed through the frameworks of tawhidic hermeneutics and the mubādalah concept as approaches to gender-relational interpretation. The findings reveal that the concept of keluarga sakinah in HPT normatively emphasizes partnership and shared responsibility between husband and wife across spiritual, educational, health, economic, and social dimensions. However, the study also identifies conceptual tensions, particularly in the emphasis on male leadership and primary financial responsibility, which may be interpreted hierarchically if not accompanied by reciprocal relational principles. Through tawhidic hermeneutics and mubādalah, marital relations within the keluarga sakinah framework can be understood as reciprocal and equitable partnerships without undermining Islamic normative foundations. This study concludes that while the HPT concept of keluarga sakinah demonstrates progressive tendencies, it requires further interpretative reinforcement to ensure consistency with the principles of justice and gender equality in Islam.